A Survey of Baby Food in Urban Area - Dalvi, C. S. (Indian Journal of Marketing, 2005)
In the changing scenario, "baby’s health" is at the top a priority to parents. Every father and mother wants to make their baby very strong and healthy. For this, parents always try to give their baby, most nutritious food. As Indian are also going for the nuclear family structure, grandmas care has reduced considerably . Also because of not having sufficient time, they can not always give their baby home prepared food. Parents are in search of readymade food for the baby without much headache. Hence, they by different types of baby food which are available in the market So to fulfill these requirements of baby food. Leading companies have introduced 12 to 15 varieties of baby food under the one brand. This survey is trying to find out the behavior of the parents in the Kolhapur urban area regarding the consumption of Baby food.